If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-(x-1)+2(x+1)=3x+1
We move all terms to the left:
2-(x-1)+2(x+1)-(3x+1)=0
We multiply parentheses
-(x-1)+2x-(3x+1)+2+2=0
We get rid of parentheses
-x+2x-3x+1-1+2+2=0
We add all the numbers together, and all the variables
-2x+4=0
We move all terms containing x to the left, all other terms to the right
-2x=-4
x=-4/-2
x=+2
| 4=4b–8 | | x+6.5=34 | | 8-q=-1 | | 44-1=7q=106 | | 5x-27=3x+5 | | 4t^2= | | 12=16-p | | 104=13n | | 8x+7x=-14+8x | | 8n^2+16n=64 | | G(-3)=-2x-3 | | 1.3x=2.4=7.6 | | 7h–5(3h–8)=–72 | | (m-1)/(-3)=-1 | | 14x-4-2x=80 | | 5(20x+50)=1,350 | | 7x-3(2x-15)=40 | | m-13/4=1 | | 6^2+x^2=10^2 | | 5 = j2+ 3 | | 4z/7-4=6 | | 3(2x-3)=37 | | 2(p-5)-9=-7 | | 2x^2-1080=0 | | -2x-1=-35 | | 8(x-1)=72 | | 42y+2=0 | | 56=41-u | | 5(x+4)+36=-3x | | x/10+2=0 | | 25=x+11 | | 3x–82=x |